The development of autism : perspectives from theory and research / edited by Jacob A. Burack ... [et al.]. - Burack, Jacob A. (Lawrence Erlbaum, 2001)
This work offers accounts of the development (typical and atypical), of persons with autism, with reference to developmental theory and research.